2007
DOI: 10.1063/1.2735934
|View full text |Cite
|
Sign up to set email alerts
|

Measured radial dependence of the peak sheath voltages present in very high frequency capacitive discharges

Abstract: The radial distribution of the measured voltage drop across a sheath formed between a 300mm electrode and an argon plasma discharge is shown to depend on the excitation radio frequency, under constant power and pressure conditions. At a lower frequency of 13.56MHz, the voltage drop across the sheath is uniform across the 300mm electrode, while at higher frequencies of 60 and 162MHz the voltage drop becomes radially nonuniform. The magnitude and spatial extent of the nonuniformity become greater with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…These effects have been studied by using analytical EM models, 6,20 a more self-consistent transmission line approach, 19,23,25 numerical simulations, 15,17,[26][27][28] and experiments. 9,10,36,37 The three main EM effects, compromising the plasma nonuniformity, are the standing wave effect, the skin effect and the edge effect. Based on these three EM effects, especially the standing wave effect, several researchers have proposed, based on theory, modeling or experiments, effective methods to suppress the EM effects and to improve the plasma uniformity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been studied by using analytical EM models, 6,20 a more self-consistent transmission line approach, 19,23,25 numerical simulations, 15,17,[26][27][28] and experiments. 9,10,36,37 The three main EM effects, compromising the plasma nonuniformity, are the standing wave effect, the skin effect and the edge effect. Based on these three EM effects, especially the standing wave effect, several researchers have proposed, based on theory, modeling or experiments, effective methods to suppress the EM effects and to improve the plasma uniformity.…”
Section: Discussionmentioning
confidence: 99%
“…A more direct evidence of the standing wave effect was presented by Barnat et al 37 by measuring the radial profile of the peak voltage drop across a sheath between a 300 mm electrode and an argon plasma. The voltage drop across the sheath was derived by the integration of the electric field within the sheath, which was measured by using laserinduced fluorescence-dip spectroscopy.…”
Section: Experimental Diagnosticsmentioning
confidence: 97%
“…Recently, several experimental [28][29][30] and theoretical [30][31][32] studies have been published on the plasma characteristics in DF CCPs sustained by VHF sources. Hebner et al 28 performed measurements in a DF 300 mm-wafer plasma processing reactor, showing that the electron density was independent of the 13 MHz bias power as it increased from 0 to 1500 W when the high frequency (HF) was fixed at 60 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…Hebner et al 28 performed measurements in a DF 300 mm-wafer plasma processing reactor, showing that the electron density was independent of the 13 MHz bias power as it increased from 0 to 1500 W when the high frequency (HF) was fixed at 60 MHz. Barnat et al 29 revealed that the radial distribution of the voltage drop across the sheath became nonuniform at the frequency of 60 MHz, and the nonuniformity was still present when a LF (13.56 MHz) source was applied to the electrode together with a HF (60 MHz) source. Bera et al 30 proved that, by a combination of computational modeling and diagnostic experiments, VHF mixing was an effective method for dynamically controlling the plasma uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…1- 10 However, when VHF is applied in a large-scale reactor having an electrode diameter greater than 30 cm, the standing-wave and skin effects become serious and limit the plasma spatial uniformity, which may affect the process characteristics. 1,2 For this reason, during the past years, VHF-CCP discharge has become the object of systematic investigations.…”
Section: Introductionmentioning
confidence: 99%